PENGARUH PEMBERIAN PERTANYAAN HIGHER ORDER THINKING SKILL (HOTS) DALAM MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI SMAN 2 PADANG - Okta Alpindo (Universitas Negeri Padang, 2014)
Objective of this research is to determine the effect of granting questions HOTS in the problem based learning to learning outcomes of 11th grade students in SMAN 2 Padang. Type of this research is quasi-experiment with Randomized Control Group Only Design. Population of this research is all of 11th grade students in SMAN 2 Padang in academic year 2013/2104. Sample of this research is 11th grade science 1 as the experimental class and 11th grade science 3 as the control class with the sampling technique is porposive sampling. Data of this research was data of learning outcomes.The data was analyzed by the mean equality test. Based on analyzis of data, we can conclude that there was granting questions HOTS in the problem based learning give significance effect to learning outcome of 11th grade students in SMAN 2 Padang for cognitive domains at significance level 5%, but there was no significance effect for affective domains at significance level 5%